IMPLEMENTASI SUPERVISI OLEH KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU - Teti Berliani (Universitas Negeri Malang, 2017)
Abstract: The purpose of this study is to describe the implementation of the supervision by the principal in improving the professionalism of teachers in schools that focus on: (1) the implementation strategy of supervision by the principal in improving the professionalism of teachers in schools; and (2) the obstacles encountered in the implementation of supervision by the principal in improving the professionalism of teachers in schools. This study used a qualitative approach with case study design. The results showed first, strategy implementation supervision by principals in improving the professionalism of teachers in schools include: scheduling carried out regularly in the implementation of supervision; supervision conducted by the principal, vice principal, senior teachers and school supervisors; supervision techniques used more emphasis on techniques classroom visits; and the evaluation of supervision activities that have been done in order to mutually discuss and exchange ideas or opinions in order to improve the process of teaching and learning in schools. And second, the obstacles encountered in the implementation of supervision by principals indicate that: (1) those aspects of concern to the supervisor in the implementation of supervision at the school include uniformity in the preparation of lesson plans, availability of teaching, ways and methods of teaching used by teachers in the teaching and learning process, media conformity lessons with teaching materials are being studied, as well as conditioning active class atmosphere and fun while teaching and learning progress; and (2) the obstacles encountered in the implementation of supervision by the principal, namely: is the fear that a teacher even shy away when they wanted to be supervised, teachers' understanding of the concept of supervision it is still very less because there are still some teachers who think that supervision is rated as the force everything that is desired by the supervisor of the teachers, the provision of follow-up of the school principal it is still not maximized because the workload reason principals outside school hours, as well as the lack of principals to provide encouragement and motivation for teachers especially in preparing teachers to be supervised. Keywords: supervision, teacher professionalism Abstrak: Tujuan penelitian ini adalah untuk mendeskripsikan tentang implementasi supervisi oleh kepala sekolah dalam meningkatkan profesionalisme guru di sekolah yang berfokus pada: (1) strategi implementasi supervisi oleh kepala sekolah dalam meningkatkan profesionalisme guru di sekolah; dan (2) kendala yang dihadapi dalam implementasi supervisi oleh kepala sekolah dalam meningkatkan profesionalisme guru di sekolah. Penelitian ini menggunakan pendekatan kualitatif dengan rancangan studi kasus. Hasil penelitian menunjukkan pertama, strategi implementasi supervisi oleh kepala sekolah dalam meningkatkan profesionalisme guru di sekolah meliputi: penjadwalan yang dilakukan secara teratur dalam pelaksanaan supervisi; supervisi dilaksanakan oleh kepala sekolah, wakil kepala sekolah, guru-guru senior dan pengawas bidang studi di sekolah; teknik supervisi yang digunakan lebih menekankan pada teknik kunjungan kelas; dan adanya evaluasi terhadap kegiatan supervisi yang telah dilakukan guna saling berdiskusi dan bertukar pikiran atau pendapat dalam rangka perbaikan terhadap proses belajar mengajar di sekolah. Dan kedua, kendala yang dihadapi dalam implementasi supervisi oleh kepala sekolah menunjukkan bahwa: (1) aspek-aspek yang menjadi perhatian supervisor dalam pelaksanaan supervisi di sekolah meliputi keseragaman dalam penyusunan rencana pembelajaran, ketersediaan perangkat mengajar, cara dan metode mengajar yang digunakan guru dalam kegiatan pembelajaran, kesesuaian media pelajaran dengan materi ajar yang sedang dipelajari, serta pengkondisian suasana kelas yang aktif dan menyenangkan saat kegiatan pembelajaran berlangsung; serta (2) kendala yang dihadapi dalam pengimplementasian supervisi oleh kepala sekolah, yakni: masih adanya rasa takut yang dimiliki oleh guru bahkan menghindar ketika hendak disupervisi, pemahaman guru mengenai konsep supervisi dirasa masih sangat kurang karena masih ada sebagian guru yang beranggapan bahwa supervisi dinilai sebagai kegiatan memaksa segala sesuatu yang dikehendaki oleh supervisor terhadap guru, pemberian tindak lanjut dari kepala sekolah dirasa masih belum maksimal karena alasan kesibukan kepala sekolah di luar jam sekolah, serta kurangnya kepala sekolah dalam memberikan semangat dan motivasi bagi guru-guru terlebih dalam mempersiapkan diri guru untuk disupervisi. Kata kunci: supervisi, profesionalisme guru   DOI: https://doi.org/10.17977/um025v1i32017p218